Analysis of the¹²C(γ, pt)2α reaction mechanism - Guryev, V.N. (Вопросы атомной науки и техники, 2007)
Calculation of the (p, t) and (α, α) energy correlations in reaction¹²C(γ, pt)2α at photon energies Eγ = 27 - 140MeV is carried out using the pole a-cluster diagram with two-spectator α) particles. These energy correlations agree with experimental data at photon energies Eγ = 32 - 50MeV. Проведено розрахунок (p, t) та (α, α) енергетичних кореляцій в реакції¹²C(γ, pt)2α з використанням полюсної α-кластерної діаграми з двомa спектаторними α--частинками при енергшї фотонів Eγ=27 - 140MeV. Ці енергетичні кореляціі узгоджуються з експериментальними даними при енергіях фотонів Eγ=32 - 50MeV. Проведен расчет (p, t) и (α, α) энергетических корреляций в реакции¹²C(γ, pt)2α с использованием полюсной α-кластерной диаграммы с двумя спектаторными α-частицами при энергии фотонов Eγ=27 - 140MeV. Эти энергетические корреляции согласуются с экспериментальными данными при энергиях фотонов Eγ=32 - 50MeV.